Harmonizing complementarities: The role of eco-innovation and globalization for achieving environmental sustainability in emerging countries - Hye, Qazi Muhammad Adnan; Abbas, Shujaat; Oad, Salochina (Energy Economics Letters, 2023)
This research study investigates the complementarity between eco-innovation and globalization in achieving environmental sustainability in emerging countries over the period of 1990 to 2021. The aim is to shed light on how these factors influence CO2 emissions. The use of the Cross Sectional Autoregressive Distributive Lag model reveals that eco-innovation, a significant catalyst for environmental advancement, demonstrates a detrimental effect on CO2 emissions, hence emphasizing its contribution to the promotion of sustainability. Interestingly, the positive interaction term between globalization and eco-innovation suggests that globalization enhances the relationship between eco-innovation and CO2 emissions. Globalization can facilitate the transfer of knowledge, technologies, and best practices across borders. In the context of eco-innovation, this means that a globalized world can promote the adoption of environmentally friendly technologies and practices more effectively. Nations that engage in active participation in global trade and knowledge exchange are likely to be more advantageous in harnessing the advantages of eco-innovation, specifically in terms of mitigating their carbon dioxide emissions. These results underscore the potential for cooperation between nations, industries, and financial institutions to drive meaningful reductions in carbon emissions, advancing environmental sustainability while maintaining economic growth. This research contributes valuable insights to policymakers, businesses, and organizations seeking a path towards a greener, more sustainable future in emerging countries and beyond.